Articaine: Opening up a New Vista for Pediatric Dentists - Ananthu H; Ashwin P Rao; Suprabha B S (Indian Journal of Forensic Medicine & Toxicology, 2021)
Lidocaine has remained the gold standard local anaesthetic agent to perform dental procedures both in theadult as well as in the pediatric patients. However, the invent of articaine has offered the clinicians with anewer and more potent local anaesthetic agent, which causes minimal side effects. Articaine is 1.5 timesmore potent and 0.6 times less toxic than lidocaine. Also, adequate anaesthesia achieved through infiltrationroute of administration of the drug, almost eliminates the need for the painful and difficult inferior alveolarnerve block in children, thereby minimising the side effects. Thus, achieving adequate anaethesia throughthe administration of a small volume of the drug has opened up a new vista for pediatric dentists in managingpain in children, although manufacturers do not recommend the usage of articaine in children less than 4years of age due to paucity of evidence. So, this review article tries to throw light on the use of articaine inpediatric patients, citing evidence from literature and also tries to portray the recent advances in the researchon articaine use in pediatric patients less than 4 years of age.